Parental Practices for Protecting Preschool Children from Air Pollution in Schools under the Chonburi Primary Educational Service Area Office 3 - Navacharoen, Aksorn; Hemchayart, Worawan (An Online Journal of Education, 2026)
This survey research aimed to examine parental practices in protecting preschool children from air pollution in two dimensions: 1) health care and 2) actions to improve air quality, within the context of Chonburi Province, an industrial area with a high risk of air pollution. The sample consisted of 153 parents of preschool children enrolled in the second semester of the 2025 academic year at a school under the Chonburi Primary Educational Service Area Office 3. The sample were selected using stratified random sampling by classroom, followed by simple random sampling within each classroom. Data were collected using a five-point Likert scale questionnaire, with a content validity index of 0.94 and a reliability coefficient of 0.93. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The findings revealed that overall parental practices were at a high level (M = 3.66, SD = 1.20). Health care practices were at a high level (M = 3.88, SD = 1.07), with the highest mean scores observed in protecting children from indoor air pollution (M = 4.10, SD = 1.01), followed by outdoor air pollution protection (M = 3.66, SD = 1.12). In contrast, practices related to actions to improve air quality were at a moderate level (M = 3.45, SD = 1.20), with environmental participation (M = 3.64, SD = 1.10) higher than support for school or relevant agency activities (M = 3.25, SD = 1.29). The findings suggest that collaboration among schools, parents, and relevant agencies should be strengthened through the development of accessible communication channels and activities, to enhance the effectiveness of air pollution prevention among preschool children.